Influence of EGF and pro-NGF on EGFR/SORTILIN interaction and clinical impact in head and neck squamous cell carcinoma - Morisse, Martin; Bourhis, Thomas; Lévêque, Romain; Guilbert, Mathieu; Cicero, Julien; Palma, Martine; Chevalier, Dominique; le Bourhis, Xuefen; Toillon, Robert-Alain; Mouawad, Francois (Frontiers in Oncology, 2023)
Head and Neck Squamous Cell Carcinoma (HNSCC) remains a cancer with a poor prognosis, with a 5-year survival rate of less than 50%. Although epidermal growth factor receptor (EGFR) is almost always overexpressed, targeted anti-EGFR therapies have modest efficacy and are mainly used in palliative care. Growth factors such as Nerve Growth Factor (NGF) and its precursor proNGF have been shown in our laboratory to play a role in tumor growth and aggressiveness. Interestingly, an interaction between Sortilin, a proNGF receptor, and EGFR has been observed. This interaction appears to interfere with the pro-oncogenic signaling of EGF and modulate the membrane expression of EGFR. The aim of this study was to characterize this interaction biologically, to assess its impact on clinical prognosis and to analyze its role in the cellular trafficking of EGFR. Using immunohistochemical staining on tumor sections from patients treated at our university center and PLA (Proximity Ligation Assay) labeling, we showed that Sortilin expression is significantly associated with reduced 5-year survival. However, when Sortilin was associated with EGFR, this association was not found. Using the Cal-27 and Cal-33 cancer cell lines, we observed that proNGF reduces the effects of EGF on cell growth by inducing the internalization of its receptor. These results therefore suggest a regulatory role for Sortilin in the degradation or renewal of EGFR on the membrane. It would be interesting in future work to show the intracellular fate of EGFR and the role of (pro)neurotrophins in these mechanisms.